More Crop Per Drop - R. Rijsberman, Frank; Giordano, Meredith; Maria Saleth, R. (IWA Publishing, 2007)
" This volume is an analytical summary and a critical synthesis of research at the International Water Management Institute over the past decade under its evolving research paradigm known popularly as 'more crop per drop'. The research synthesized here covers the full range of issues falling in the larger canvas of water-food-health-environment interface. Besides its immediate role in sharing knowledge with the research, donor, and policy communities, this volume also has a larger purpose of promoting a new way of looking at the water issues within the broader development context of food, livelihood, health and environmental challenges. More crop per drop: Revisiting a research paradigm contrasts the acquired wisdom and fresh thinking on some of the most challenging water issues of our times. It describes new tools, approaches, and methodologies and also illustrates them with practical application both from a global perspective and within the local and regional contexts of Asia and Africa. Since this volume brings together all major research works of IWMI, including an almost exhaustive list of citations, in one single set of pages, it is very valuable not only as a reference material for researchers and students but also as a policy tool for decision-makers and development agencies. "